How tissue T1-variability influences DCE-MRI perfusion parameters estimation of recurrent high-grade glioma after surgery followed by radiochemotherapy. (September 2022) - Filice, Silvano; Ortenzia, Ornella; Crisi, Girolamo
Background: Quantification of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) kinetic parameters (KPs) requires a determination of native tissue T1. Two approaches are adopted: (i) tissue T1-maps are acquired; and (ii) an a priori T1 value (fT1) is fixed for all patients (fT1-approach). Although it is more attractive, the fT1-approach might bias the results of KP calculations due to tissue T1 variability. Purpose: To quantify the tissue T1 variability of recurrent high-grade glioma (HGG) and the error in KP estimation when the fT1-approach is adopted. Material and Methods: We reviewed the postoperative MRI scans of 28 patients with recurrent HGG after radiochemotherapy. MRI study included T1-maps from multiple-dynamic multiple-echo imaging, DCE-MRI, and contrast enhanced T1-weighted images. KPs were calculated using T1-map and fT1-approach. Results: The tissue T1 variability of recurrent HGG was relevant. The absolute error in KP estimation, as a function of the deviation of fT1 from the true value, was 8% every 100 ms. The difference between the KPs obtained with fT1-approach from fT1 values of 1300, 1390, and 1500 ms and their reference values were mostly within the 95% confidence interval (± 1.96 standard deviation). Conversely, using fT1 values of 900, 1200, 1600, and 1900 ms causes a significant error in KP estimation ( P <0.05). Conclusion: Recurrent HGG is characterized by a substantial T1 variability. Although the fT1-approach does not account for this variability, it results in a minor effect on the KP estimations provided the fT1 value is in the range of 1300–1500 ms.